Breastfeeding and Becoming a Mother : Influences and Experiences of Mothers of Preterm Infants - Flacking, Renée (Uppsala universitet, Institutionen för kvinnors och barns hälsa, 2007)
The overall aim of this thesis was to expand the knowledge and understanding of the processes of breastfeeding and becoming a mother in mothers of preterm infants. For this purpose, in-depth interviews were conducted with 25 mothers, whose very preterm infants had received care in seven neonatal units (NU) in Sweden, 1-12 months after discharge (I-II). In addition, prospective population-based register studies were performed of infants born 1993-2001; among 35 250 term and 2093 preterm infants (III), and a subpopulation of 225 very preterm infants (IV). Data were obtained from the Child Health Service registry of breastfeeding in Uppsala and Örebro, the Medical Birth Registry, and Statistics Sweden. The experiences of mother-infant separation, institutional authority, emotional exhaustion and disregard of breastfeeding as a relational interplay, comprised major hindrances to mothers’ experiences of breastfeeding as reciprocal and of a secure mother-infant relation, during and after the discharge from an NU (I-II). All studied socioeconomic factors, i.e. lower educational level, receiving unemployment benefit or social welfare or having a low equivalent disposable income, were individually adversely associated with breastfeeding up to six months of infants’ postnatal age, but were not found more decisive for weaning in mothers of preterm infants compared to those of term infants (III). Preterm infants were breastfed for a shorter time than term infants (III), but a long breastfeeding duration was evident. In addition, gestational age and neonatal disorders were not associated with breastfeeding duration in very preterm infants (IV). In conclusion, this thesis shows that improvements in the NU environment and the caring paradigm are called for. Furthermore, as socioeconomic status clearly has an impact on breastfeeding duration, increased equity in health care in accordance with the individuals’ needs must be sought, where resources are allocated to ensure fulfilment of needs in more vulnerable mothers and infants.